Lack of Epstein-Barr virus infection in cervical carcinomas - Oliveira, Deilson Elgui de [UNESP]; Monteiro, TAF; de Melo, W. A.; Moreira, MAR; Alvarenga, M.; Bacchi, C. E. (College Amer Pathologists, 1999)
Context.-The Epstein-Barr virus (EBV) is a ubiquitous microorganism strongly associated with lymphoproliferative disorders and a large number of human neoplasms, mainly undifferentiated nasopharyngeal carcinoma and Burkitt lymphoma. The viral DNA has been detected in other tumors, such as carcinomas from tonsil, salivary glands, and thymus, and malignancies of the female genital tract. Some authors have proposed that EBV could play a role in the carcinogenesis of cervical tumors; however, other studies do not support this hypothesis.Objective.-To assess whether EBV is associated with female genital tract neoplasms.Design.-Sixty-five biopsy specimens (5 in situ carcinomas, 24 invasive squamous cell carcinomas, 6 lymphoepithelioma-like carcinomas, and 30 endocervical adenocarcinomas) were used to perform EBV detection through RNA in situ hybridization.Results.-None of the cervical carcinoma cases studied was positive for EBV infection.Conclusions.-The results suggest that it is still premature to incriminate EBV in the carcinogenesis of cervical carcinoma.